Neuronal activity topography (NAT) analysis of EEG can predict neurocognitive deterioration earlier than FDG‐PET: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Ishii, Kenji; Tanaka, Mieko; Watanabe, Yuri; Sano, Akiko; Kobayashi, Yohei; Ishibashi, Kenji; Wagatsuma, Kei; Asada, Takashi; Kosugi, Yukio
Abstract: Background: We recently reported that FDG‐PET can predict neurocognitive deterioration three years earlier than cognition in our aging cohort. This study examined whether EEG detects the deterioration as early as FDG‐PET. Method: Two groups of subjects' data‐set with normal PET/cognition were selected from our cognitively normal (CN) elderly cohort who participated in the same‐day EEG and FDG‐PET annually. The NLC group (n = 41, age = 75.2±4.7y, MMSE = 29.3±1.1) consists of those whose PET findings remain normal for more than three successive years. NL2 group (n = 22, age = 75.1±4.9y, MMSE = 29.0±1.5) consists of those whose PET findings deteriorate within three years. Each PET image was classified into five ranks (A/A‐/B/B‐/C) by visual and statistical analysis and A/A‐ were regarded as normal. The results of neuropsychological tests (MMSE, HDS‐R, MoCA) and Neuronal Activity Topography (NAT) analysis indices derived from five minutes EEG record at rest with eyes closed were compared between the two groups. Result: The average value of the two groups is significantly different in (1) the index sNAT value based on the power spectrum of the EEG, (2) the index vNAT value based on the power ratio of the sNAT values of adjacent frequency subbands, and (3) the mean power frequency of the occipital region (sNATNLC = ‐0.077±0.071, sNATNL2 = ‐0.022±0.103, p = 0.03* ; vNATNLC = ‐0.080±0.076, vNATNL2 = ‐0.038±0.059, p = 0.03* ; MPFNLC = 9.29±0.48Hz, MPFNL2 = 8.97±0.55Hz, p = 0.02*). In the NL2 group, a significant negative correlation was found between vNAT value and MMSE, and MoCA (CORvNAT‐MMSE = ‐0.43, p = 0.05* ; CORvNAT‐MoCA = ‐0.59, p < 0.01**. Above findings suggest that the signs of cognitive deterioration in near future is detectable using NAT analysis. Conclusion: In cognitively normal subjects whose PET findings start to deteriorate in the next following years, signs of deterioration are already detectable with NAT analysis of EEG. This suggests that the alteration of neuro‐electrical activity may precede the decline of cerebral glucose metabolism. Further study with larger groups is necessary.